Two Ways to Remain in Jesus: Bearing Fruit and Becoming His Disciple - Au, Trung Thinh (Khoa Học Công Giáo và Đời Sống, 2021)
Remaining in Jesus, in God, that is the main content of John's 15 gospel chapter. In the parable of the true vine (1-8), John shows the importance of remaining in Jesus like a branch with a vine(5). Besides, he also showed that there are ways and what to know that we remain in Jesus. according to John, there are two ways remain in Jesus that is bearing fruit and becoming His disciple. And when we are pruned, cleaned and asked whatever that is the sign to know we remain in Jesus.